Telemodernities television and transforming lives in Asia - Lewis, Tania; Martin, Fran 1971-; Sun, Wanning 1963- (Duke University Press, 2016)
Introduction: telemodernities -- Lifestyle television in context : media industries, cultural economies, and genre flows -- Local versus metropolitan television in China : stratification of needs, taste, and spatial imagination -- Here, there, and everywhere : mediascapes, geographic imaginaries, and indian television -- Imagining global mobility : TlC Taiwan -- Gurus, babas, and daren : popular experts on Chinese and Indian advice TV -- Magical modernities : spiritual advice TV in india and taiwan -- Risky romance : navigating late modern identities and relationships on Chinese and Indian Lifestyle TV -- A self to believe in: negotiating femininities in Sinophone lifestyle advice TV -- Conclusion: negotiating modernities through lifestyle television
Includes bibliographical references and index. - Description based on print version record
Keywords: Reality television programs / China; Reality television programs / India; Reality television programs / Taiwan; Lebensstil -- Motiv; Reality-TV; China; Taiwan; Indien